Prognostic Importance of Changes in Cardiac Structure and Function in Heart Failure With Preserved Ejection Fraction and the Impact of Spironolactone. (November 2015) - Shah, Amil M.; Claggett, Brian; Sweitzer, Nancy K.; Shah, Sanjiv J.; Deswal, Anita; Anand, Inder S.; Fleg, Jerome L.; Pitt, Bertram; Pfeffer, Marc A.; Solomon, Scott D.
Abstract : Background—: Limited data exist regarding the impact of aldosterone antagonist therapy on cardiac structure and function in heart failure with preserved ejection fraction and on the prognostic relevance of changes in cardiac structure and function in heart failure with preserved ejection fraction. Methods and Results—: Cardiac structure and function were assessed by quantitative echocardiography at baseline and at 12- to 18-month follow-up in 239 patients with heart failure with preserved ejection fraction (left ventricular [LV] ejection fraction [LVEF] ≥45%) enrolled in the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist (TOPCAT) trial. The impact of spironolactone therapy on measures of cardiac structure and function was assessed in the study population overall, and change in echocardiographic measures was associated with the subsequent occurrence of the primary composite outcome of cardiovascular death, heart failure hospitalization, or aborted cardiac arrest. Spironolactone was not associated with alterations in cardiac structure and function compared with placebo. Decrease in left atrial volume at follow-up was associated with a lower risk of subsequent occurrence of the primary outcome. Conclusions—: Twelve to 18 months of spironolactone therapy was not associated with alterations in cardiac structure or function in patients with heart failure with preserved ejection fraction. Reduction in left atrial volume at follow-up was associated with a lower risk of subsequent occurrence of the primary composite outcome. Clinical Trial Registration—: URL:http:///www.clinicaltrials.gov . Unique identifier: NCT00094302. Abstract : Supplemental Digital Content is available in the text.